A Look Into The Historical Novel (Raparin Journal of Humanities (RJH), 2020)
The historical novel— also referred to as ‘historical fiction’ in this paper— is a popular genre of literature and currently one of the rich areas for research within the fields of literature and literary criticism. Although historical novels are usually densely written and filled with factual details, they can effectively bring a historic period to life in engaging and memorable ways. Historical fiction has received so much attention over the years and it has been greatly discussed by scholars, yet one can hardly find a comprehensive definition for it that includes all the characteristics of the genre. This paper investigates the reasons behind this and analyzes some of the definitions of historical fiction in an attempt to form a working definition for the genre. It also studies whether research guarantees the success of a historical work of fiction or not. The paper also explains the purposes behind the production of historical fiction. Clearly, this genre has a long history in world literature also and to have a thorough understanding of it, one may need to look at its background and key practitioners as well. A section of this paper attempts to do that in detail. Besides all the difference historical fiction has made to the world of literature as well as the lives of its readers, several of its aspects have been criticized by scholars. Looking at the criticism is another way to better understand this particular type of narrative.